Effects of Tourism Development on Land Use in the Coastal Area of Surabaya City - Kartika Eka Sari; N Sari (TATALOKA, 2020)
Surabaya is the capital city of East Java Province that develops coastal tourism activities. Based on Surabaya City RTRW for 2014-2034, the development of coastal tourism in Surabaya is in Bulak District. The district is designated as a development unit III of Tambak Wedi that directed as marine beach tourism. Kenjeran Tourism has a number of tourist destinations including Kenjeran Beach, THP Kenjeran, Kenjeran Park, Bulak Park, Surabaya Park, and Kenjeran Bridge.he development of coastal tourism resulted in many changes in land use and building’s function, mainly affecting the type of land use settlement because people tend to use the front of the house for trading activities and services. This study aims to determine the effect of tourism development on land use in the Kenjeran Area. This study uses overlay analysis and PLS (Partial Least Square) analysis. The results of this study found that tourism development variables affect land use change by 92.2%. Changes in land use are dominated by vacant land and supporting facilities for tourism activities such as trade and services, recreation, tourism, and green open space